CONCEPTUAL STUDY OF KLOMA WITH SPECIAL REFERENCE TO MEDIASTINUM - Shah Rupal; Shendye Swarali (International Journal of Applied Ayurved Research, 2020)
In Ayurveda texts 13 srotasa have been described. One of them is udakavaha srotas. The udakavaha srotas, consists of the various channels which maintain the fluid balance of the body derive their origin from two places - Talu (The hard and soft palates) and Kloma. This age old authentic science seems incomplete as it has being either destroyed or carried away from our country by invaders. This results into a lacuna giving rise to controversies and a limitation to our evaluating, analysing and understanding capability. Out of many of such unresolved aspects there is a term called Kloma, which along with Talu is the moolshthana or originating point of Udakavaha Srotas.